Parahippocampal Involvement in Mesial Temporal Lobe Epilepsy with Hippocampal Sclerosis: A Proof of Concept from Memory-Guided Saccades - Colnaghi, Silvia; Beltrami, Giorgio; Poloni, Guy; Pichiecchio, Anna; Bastianello, Stefano; Galimberti, Carlo Andrea; Versino, Maurizio (Frontiers in Neurology, 2017)
Objective: Mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS) may involve extrahippocampal areas of structural damage and dysfunction. The accuracy of medium-term spatial memory can be tested by Memory Guided Saccades (MGS), to evaluate a functional impairment of the parahippocampal cortex, while Voxel Based Morphometry (VBM) analysis can be used to detect a structural damage of the latter region. Methods: MGS with 3 and 30 second memorization delays were compared between 7 patients affected by right MTLE-HS, 6 patients affected by left MTLE-HS, and 13 healthy controls. The same subjects underwent brain MRI for a VBM analysis. Correlation analysis was performed between the results of VBM and MGS and with patients’ clinical data. Results: Right MTLE-HS patients showed impaired accuracy of leftward MGS with a 30 second memorization delay; their grey matter volume was reduced in the right hippocampus and inferior temporal gyrus, and bilaterally in the cerebellum. Left MTLE-HS patients had normal MGS accuracy; their grey matter volume was reduced in the left hippocampus, in the right inferior temporal gyrus and corpus callosus, and bilaterally in the insular cortex and in the cerebellum. The difference between right and left parahippocampal volume correlated with MGS accuracy, while right and left hippocampal volume did not. Hippocampal and parahippocampal volume did not correlate with clinical variables such as febrile seizures, age at disease onset, disease duration and seizure frequency. Conclusions: MGS abnormalities suggested the functional involvement of the right parahippocampal cortex in patients with right MTLE-HS, supporting a right lateralization of spatial memory control and showing a relation between functional impairment and degree of atrophy.